IDENTIFIKASI POTENSI KOMODITI TANAMAN PANGAN DALAM MENDUKUNG KETAHANAN PANGAN DI KABUPATEN SEMARANG - Eka Dewi Nurjayanti; Endah Subekti (Universitas Wahid Hasyim, 2017)
This study aims to identify the classification of food crops in the position of the regional economy in support of food security Semarang regency. Methods of data analysis is to determine the classification of food crops in the district of Semarang using Klassen Typology approach. Production of paddy in 2013 until 2015 always increase production. The increase in production is supported by the improvement of irrigation facilities, the provision of seeds, insecticides and fertilizers as well as farmers' cropping pattern is expected to boost rice production. As for crops that are developed in the district of Semarang are corn, soybean, cassava, sweet potatoes, and peanuts. Classification of agricultural commodities in the district of Semarang using Klassen Typology analysis resulted in four classifications of agricultural commodities as follows: (1) Prima Commodity (rice); (2) Development Commodities (cassava and yam); (3) Potential Commodity (corn); (4) Retarded Commodities (soybeans and peanuts).Keywords: commodity, food crops, Klassen Typology